Is the reproductive potential of wild house mice regulated by extrinsic or intrinsic factors? - Jacob, J.; Hinds, L.A.; Singleton, G.R.; Sutherland, D.R.; Ylönen, H. (Wiley, 2007)
The regulation of reproductive performance in small mammals may be determined by extrinsic or intrinsic parameters. In a large‐scale, replicated field experiment we monitored the seasonal fluctuation in food availability and tested the effects of food addition on the reproductive performance of wild house mice (Mus domesticus) in south‐eastern Australia. Ovulation rates and litter size increased during spring and peaked in October/November. Ovulation rate was consistently higher than litter size by approximately 1.2 embryos (19%). None of the extrinsic parameters measured (food quality and quantity, mouse abundance) had an impact on reproductive performance. The addition of food did not prevent the mid summer decrease in ovulation rates nor did it alter the difference between ovulation rates and litter size. While the number of previous pregnancies did not affect reproductive performance, the age of mice did: older mice tended to have higher ovulation rates than younger mice. The effect of age‐dependent changes in ovulation rates on population growth rates of house mice seemed to be of limited importance. We conclude that the reproductive output in wild house mice is determined by ovulation rates and not by litter size. The regulation of ovulation rates through an intrinsic factor (age) seems evident but the importance of food availability and house mouse abundance for ovulation rates is low.